The Electoral History of the Post-Soviet Crimea: from UkSSR to Russia - A. A. Tokarev (Vestnik MGIMO-Universiteta)
Abstract: One year ago, the referendum was held in the Ukrainian autonomous republic of Crimea which resulted in the peninsula becomino part of Russia. This article discusses all Crimean voting, including referendums and elections: from the first referendum in the history of the Soviet Union in January 1991, to the last election to the State Council of the Republic of Crimea within the Russian Federation in September 2014. For each vote, except for the regional elections, the average results of the main candidates are presented in the Crimea and in Ukraine. Sevastopol always has particular identity and special administrative status of the city, regardless of the sovereign center title (Moscow or Kyiv). That`s why we give the data for Sevastopol in addition to the Crimea for each vote. The author analyzes the voting results and compares them with those in other south-eastern regions of Ukraine. A special Crimean identity postulates in this case and changing of regional political trends in Ukraine in the mid-2000s are given. After 2002, Donetsk and Luhansk regions provided 70-100% of support to ”Party of Regions“ and its leader. While their main rivals always received minimum points from the Donbass. Crimea and Sevastopol were always in second position supporting the ruling party until the end of their Ukrainian history. For a visual comparison of the difference in votes of the Crimea, Sevastopol and the whole Ukraine, the author offers the original graph. In addition, the article focuses on the results and sociological basis of the last Crimean referendum held in March 2014. On the one hand its procedure creates many questions: the lack of equality in the agitation, the presence of paramilitaries, the vote in the absence of actual voter lists, etc. On the other hand, there are, at least, 4 researches of Ukrainian and American sociological services, according to which the sovereignty of Russia is a real value perceived by the majority of Crimea and Sevastopol citizens.